Media in the Aspect of Cultural and Creative Industries - Tomova, Bilyana (Research Papers, 2014)
The object of this study is the media - radio, television and new media, print media will be presented only for comparative analysis. Subject is their positioning as an element of the concept of cultural and creative industries, and for this purpose they are covered at the macro level and measured as economic activities observed by SBS, as creators of economical contribution. Research task is based on the current scarcity of macroeconomic data releases as a specific economic subject - a fact limiting the opportunity for an overall picture of this market. In this analysis, this was achieved by theoretical and methodological framework is based on the concept of CCIs and in which the object (theoretical) is defined (statistically) based cultural content of the activity. This allows the media to cover the macro level and attempt a systematic evaluation (in terms of the national economic system) in the national media market and the relevant submarkets and activities as creators of economical contribution.